Analysis of Legal Protection for Land Rights Holders in Determining Compensation Related to Land Acquisition for Public Interest Based on Justice Values - Yuda, Dela Fatma; Djunaedi, Djunaedi (Jurnal Konstatering, 2025)
Land acquisition for public interest often triggers conflicts and land problems, especially in the process of compensation for land rights holders which in its implementation tends to be inappropriate and unfair to land rights holders. The purpose of this study is to determine and analyze legal protection for land rights holders in determining compensation for land acquisition for public interest based on justice and to determine and analyze the legal consequences for land rights holders in determining compensation for land acquisition that is not in accordance with public interest based on justice. The type of research used in conducting this study is Normative juridical. Legal protection for land owners in land acquisition for public interest is realized through the provision of appropriate compensation based on Article 33 of Law No. 2 of 2012, with an assessment covering land, space above and below ground, buildings, plants, objects related to land, and other losses. However, the practice of compensation often harms land owners, so supervision is needed to ensure that the process is fair and in accordance with regulations. This supervision is important to prevent misappropriation and ensure the protection of land owners' rights legally.